Relationship between anxiety and tension type headache among medical student - Tarigan, Nisa Nathalia; Fresia, Ana; Lubis, Adhayani (Buletin Kedokteran & Kesehatan Prima, 2024)
Tension-type headache (TTH) is one of the most common types of primary headaches experienced by all age groups worldwide. The incidence of TTH among the medical students was also high. This study aimed to identify the relationship between anxiety and the incidence among medical students. We used an analytical descriptive research design and a cross-sectional study approach. A total of 119 students from Prima Indonesia University Faculty of Medicine participated in this study. Data were collected using the Back Anxiety Inventory (BAI) questionnaire to measure anxiety levels and Headache Screening Questionnaire (HSQ) to measure the incidence of TTH. The results of data analysis using the chi-square test showed a significant relationship between anxiety levels and the incidence of TTH (p = 0.026). This finding indicates that the higher a person's anxiety level, the more likely they are to experience TTH. Based on the results of the study, 84.87% (101 people) of the participants experienced TTH, while 15.13% (18 people) experienced possible TTH. The majority of the participants with high anxiety levels were female (94.4%). It can be concluded that there is a significant relationship between anxiety and the incidence of TTH among Prima Indonesia University Faculty of Medicine students in 2023. This finding supports the hypothesis that anxiety is a risk factor of TTH.